Mapping Contemporary Studies on Shaykh Ihsan Jampes and Future Directions for Pesantren-Based Qur’anic Exegesis: A Systematic Literature Review - Cholid Ma'arif; Sujiat Zubaidi; Muhammad Chirzin; Zahratur Rofiqah Binte Mochammad Sandisi (Universitas Islam Negeri Syekh Wasil Kediri, 2026)
This article maps contemporary studies on Shaykh Ihsan Jampes, an Indonesian pesantren scholar from Kediri, whose Arabic works occupy an important position in the pesantren intellectual tradition. It examines their future directions for pesantren-based Qur’anic exegesis. Using a systematic literature review, this study shifts the discussion from a broad figure-centered mapping of Ihsan scholarship to a more focused synthesis of tafsir-related studies. The data consist of 67 academic sources collected through keyword searches, screening, and citation chaining. Of these, 27 studies were selected as the core corpus for their strong relevance to Ihsan Jampes, Sirāj al-Ṭālibīn, pesantren turāth, and their potential for tafsir-oriented analysis. The units of analysis include exegetical method, exegetical orientation, verse usage, intertextual sources, the relationship between Sufism and meaning construction, and future directions for pesantren-based Qur’anic exegesis. The findings show that existing scholarship on Ihsan Jampes has been dominated by Sufism, pesantren education, and intellectual networks. However, several studies have opened significant pathways for tafsir research through intertextuality, maqāṣid al-Qur’ān, ishārī reading, and verse-based sharḥ in Sirāj al-Ṭālibīn. This article argues that Ihsan Jampes’s main contribution to tafsir studies lies not in a formal, complete commentary, but in embedded exegesis within the pesantren sharh tradition. Based on this synthesis, the article proposes an initial model of pesantren-based Qur’anic exegesis grounded in sharḥ al-ayat, combining sanad authority, intertextual reading, ethical orientation, maqāṣid, and contextual Muslim needs.